The association of gegenhalten in the upper limbs with dyspraxia. Issue 7 (July 1988) - Tyrrell, P; Rossor, M
Abstract : Ten patients with gegenhalten of the upper limb of mixed aetiology were studied, in nine of whom an association with dyspraxia was found. In four of the patients, the rigidity became more pronounced after the instruction to relax, and only one patient showed improvement after this instruction. In these patients, the resistance to movement, evident as gegenhalten, may be a direct consequence of the dyspraxia.